Field evaluation of Carifend® net for the protection of stored tobacco from storage insect pests. (March 2019) - Athanassiou, C.G.; Rumbos, C.I.; Stephou, V.K.; Sakka, M.; Schaffert, S.; Sterz, T.; Bozoglou, C.; Klitsinaris, P.; Austin, J.W.
Abstract: In the present study, Carifend ® an alpha-cypermethrin-coated net, was evaluated for the control of Lasioderma serricorne and Ephestia elutella in semi-field and field tests in two storage facilities. In the semi-field tests, three Carifend ® Multi-Cubicles (CMCs), within which one carton box filled with tobacco was placed, were suspended in three separate rooms. Two MoBe traps were placed, one inside and one outside of each CMC. Three additional tobacco quantities in similar carton boxes, with a MoBe trap on them, were placed in three separate adjacent rooms and served as controls. In each room, 50 L. serricorne and 50 E. elutella adults were released outside of each tobacco quantity and the traps were inspected at weekly intervals for 3 weeks. A similar approach was followed in the field test conducted in a commercial tobacco storage facility. However, no insects were released and the test was based on the naturally-occurring immigrations of populations of E. elutella and L. serricorne from outside the facility or from unprotected tobacco. In semi-field tests, significantly more adults were captured in the first week in the control traps compared to counts from CMCs, either inside or outside. However, differences were significant only in the case of E. elutella. Only one single L. serricorne individual was found in the traps that had been placed inside CMCs, whereas no adult E. elutella were detected inside CMCs. In the field-test, traps that had been placed inside the CMCs captured only 3 and 1 adults of E. elutella and L. serricorne, respectively, during the entire survey period. Results of this study show that Carifend ® is highly effective for the control of both species on stored tobacco, and could be further successfully utilized as an alternative method over the use of traditional insecticidal treatments (such as repeated fumigations of phosphine gas) on tobacco. Highlights: Carifend ®, a net that contains alpha-cypermethrin, was evaluated against stored tobacco pests. Carifend ® was effective against Lasioderma serricorne and Ephestia elutella on stored tobacco. Protection of tobacco was continuous for a long storage period. Captures of both species were recorded in the treated facility right after the fumigation with phosphine.